A new species of the Cyrtodactylus (Geckoella) collegalensis (Beddome, 1870) complex (Squamata: Gekkonidae) from Western India - Agarwal, Ishan; Mirza, Zeeshan A.; Pal, Saunak; Maddock, Simon T.; Mishra, Anurag; Bauer, Aaron M. (Zootaxa, 2016)
A new species of Cyrtodactylus (Geckoella) from the C. collegalensis complex is described based on a series of specimens from western and central India. Morphological and molecular data support the distinctiveness of the new form, which can be diagnosed from other Cyrtodactylus (including other Geckoella) species by its small body size (snout to vent length to 56 mm), the absence of precloacal and femoral pores, no enlarged preanal or femoral scales, and a dorsal scalation consisting wholly of small, granular scales. The new species is most closely related to C. collegalensis, C. speciosus and C. yakhuna, from which it differs by the presence of a patch of enlarged roughly hexagonal scales on the canthus rostralis and beneath the angle of jaw, its relatively long limbs and narrow body, and a dorsal colour pattern of 4–6 pairs of dark spots.